ANALISA PERSEPSI PELANGGAN TERHADAP KINERJA AGEN PROPERTI DAN PENGARUHNYA TERHADAP KEPERCAYAAN DI SURABAYA - Mulya, Anne Christanti (Jurnal Strategi Pemasaran, 2014)
This research is causality research typeand discusses the dimensions of Job Performance,which are Task Performance, ContextualPerformance and Adaptive Performance. Thatdimensions are thought to affect customer trust inSurabaya. This research uses quota samplingmethod, with samples of 100 customers who lived inSurabaya and had used property agents services orconduct transactions through property agents. Theresult of this study indicates that all dimensionssimultaneously have a significant impact to the trustof property agent consumers. But partially, AdaptivePerformance has a positive and significant andinterpersonal adaptation as the most influenceindicator.